Displaying Of Green Fluorescent Protein On A Recombinant Bacteriophage Infecting Escherichia Coll Atcc 11303 - Ong, Jia Wei (2017)
Phage display technology allows the presentation of foreign peptides on the surface of a bacteriophage. Phage display technology is used to acquire the function of the displayed peptides which was not present on wild type bacteriophage. Using phage display technology, a recombinant phage would be constructed as a model for future manipulation. The technology was applied to display a green fluorescence protein (GFP) on tail protein of Escherichia Phage YD-2008.S to create GFP labelled recombinant bacteriophage.